TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA - Rochman (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Victims of cases of domestic violence that mostly occur in women should get more serious attention from the community and the government. This study aims to identify and analyze the factors that cause the occurrence of criminal acts of domestic violence. Domestic violence, especially violence perpetrated by a husband against his wife, does not only cause physical suffering but also psychological suffering. Therefore, victims of domestic violence must receive maximum protection, Article 44 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is the basis for deciding perpetrators of acts of domestic violence. This research method uses a normative juridical approach, namely research that focuses on library research, the results of this study are that domestic violence occurs mostly in women, the factors that cause domestic violence are mostly due to gender equality factors and economic factors.